A Measured Approach to Ending Poverty and Boosting Shared Prosperity : Concepts, Data, and the Twin Goals - World Bank Group (Washington, DC: World Bank, 2014)
In 2013, the World Bank Group adopted two new goals to guide its work: ending extreme poverty and boosting shared prosperity. More specifically, the goals are to reduce extreme poverty in the world to less than 3 percent by 2030, and to foster income growth of the bottom 40 percent of the population in each country. While poverty reduction has been a mainstay of the World Bank’s mission for decades, the Bank has now set a specific goal and timetable, and for the first time, the Bank has explicitly included a goal linked to ensuring that growth is shared by all.